2021
DOI: 10.3390/wevj12010015
|View full text |Cite
|
Sign up to set email alerts
|

Social Aspects of Electric Vehicles Research—Trends and Relations to Sustainable Development Goals

Abstract: E-mobility sustainability assessment is becoming more comprehensive with research integrating social aspects without focusing only on technical, economic, and/or environmental perspectives. The transportation sector is indeed one of the leading and most challenging greenhouse gas polluters, and e-mobility is seen as one of the potential solutions; however, a social perspective must be further investigated to improve the perception of and acceptance of electric vehicles. This could consequently lead to the Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…This is one reason why new research in the area of SDGs with a purpose and goal to find new insights, regardless of the study area, is crucial. This research focuses on the logistics and supply chain sector but might also be related to other cases, for example, stakeholder perception towards hydrogen energy [153], electric vehicles [154], etc.…”
Section: Discussionmentioning
confidence: 99%
“…This is one reason why new research in the area of SDGs with a purpose and goal to find new insights, regardless of the study area, is crucial. This research focuses on the logistics and supply chain sector but might also be related to other cases, for example, stakeholder perception towards hydrogen energy [153], electric vehicles [154], etc.…”
Section: Discussionmentioning
confidence: 99%
“…The European Green Deal [3] declared the need to provide "more affordable, accessible, healthier and cleaner alternatives" to the current mobility practices of European citizens to achieve sustainable transport means. Citizens and, more broadly, all users have a central role in the transition towards sustainable mobility [33]. Hence, this research investigates the propensity to choose an EV, exploring how a citizen contributes to the transition towards sustainable mobility, which sociodemographic characteristics show who chooses an EV, which current mobility habits exist, and how these habits affect the propensity to adopt EVs.…”
Section: Sociodemographic Characteristics and Daily Practicesmentioning
confidence: 99%
“…In the context of what has been discussed in the preceding paragraph on the challenges of ever-increasing carbon emissions, many studies indicate that the need to change the propulsion system and convert to electric vehicles (EVs) presents the world with a solution to attain a sustainable future [6][7][8][9][10]. A lot of research has focused on electrifying passenger cars as they contribute to over 90% of the transport emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this class presents an opportunity for massive gains in the fight against the increasing greenhouse gas effect [11]. There are a number of studies all over the world that have shown that conversion to EVs would mitigate GHG emissions from the transport sector [10,12,13]. Electric vehicles available in the current market differ according to their degree of hybridization, starting with hybrid vehicles with limited battery power to fully-electric vehicles with enhanced battery power, corresponding to varying mitigation potential [14].…”
Section: Introductionmentioning
confidence: 99%